2000
DOI: 10.1046/j.1365-263x.2000.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration of an avulsed primary incisor. A case report

Abstract: A 7-year-old girl had injured her maxillary primary incisors in a playground. One of the already-mobile incisors had been avulsed. The child who had a cough and breathing difficulties during sleep was diagnosed as suffering from upper respiratory infection and was treated with antibiotics. A few days later because her body temperature was elevated a chest radiograph was taken. The radiograph revealed an aspirated tooth in her right bronchus with atelectasis of the lower lobe. The tooth was removed by bronchosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 9 publications
3
18
0
1
Order By: Relevance
“…Although the reason is not clarified, this action should be encouraged as it helps to judge that the tooth is not swallowed or inhaled by the child [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason is not clarified, this action should be encouraged as it helps to judge that the tooth is not swallowed or inhaled by the child [27].…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion occurs in adults too but is most of the times accidental; or it occurs in psychiatric patients or iatrogenic reasons when rubber dam is not used. In dental operatory, the ingested foreign body may include teeth, restorations, restorative materials, instruments, rubber dam clamps, gauze packs, and so forth [1][2][3]. Similar case studies have also been reported previously [4].…”
Section: Introductionmentioning
confidence: 75%
“…El examen intraoral empieza con la observación de los tejidos blandos, verificando el estado de los labios, mucosa y encías. Es importante verificar que no haya fragmentos de dientes enterrados en la mucosa o que de forma accidental el paciente haya ingerido o inhalado la pieza dentaria avulsionada (13,14).…”
Section: Examen Estomatológicounclassified